Furniture care and maintenance - Smithonian Institution; Conservation Analytical Laboratory (EE.UU.). Smithonian Institution (Arlington, VA : Cinemasound Video Productions, 1994)
El video trata de la conservación y restauración de muebles y objetos de madera.
Estereo
Directed by Marcus K. West ; written by Donald C. Williams ; narrated by Paul Morella
Keywords: MUEBLES EN MADERA; RESTAURACION DE MUEBLES; VIDEOGRABACIONES